Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper provides a semi-annual review of the status of financing for PRGF-ESF lending, subsidization of emergency assistance, and HIPC and MDRI debt relief. The last review was completed by the Executive Board on September 24, 2008. The paper does not address the G-20's recent call for additional concessional resources, which is discussed in a separate paper.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet